Chinese and Indian Merchants in Modern Asia: Networking Businesses and Formation of Regional Economy - Choi, Chi-cheung; Oishi, Takashi; Shiroyama, Tomoko (BRILL, 2019)
Chinese and Indian Merchants in Modern Asia studies overseas Chinese and Indian merchants and their impacts on the emerging global economy from the nineteenth to twentieth centuries, focusing on their networking and interactions with the empires and the states.
Google-Books-ID: Hh24DwAAQBAJ
Keywords: History / Asia / General; History / Middle East / General; History / Social History; Social Science / Ethnic Studies / General